Helping Fellow Beings: Anthropomorphized Social Causes and the Role of Anticipatory Guilt. (January 2014) - Ahn, Hee-Kyung; Kim, Hae Joo; Aggarwal, Pankaj
People are often reluctant to comply with social causes because doing so may involve personal sacrifices of time, money, and effort for benefits that are shared by other members of society. In an effort to increase compliance, government agencies and public institutions sometimes employ financial tools to promote social causes. However, employing financial tools to induce prosocial behavior is expensive and often ineffective. We propose that anthropomorphizing a social cause is a practical and inexpensive tool for increasing compliance with it. Across three prosocial contexts, we found that individuals exposed to a message from an anthropomorphized social cause, compared with individuals exposed to a message relating to a nonanthropomorphized social cause, were more willing to comply with the message. This effect was mediated by feelings of anticipatory guilt experienced when they considered the likely consequences of not complying with the cause. The theoretical and practical implications of these findings are discussed.